Socio-Demographic and Morbidity Profile of Slum Area in Ahmedabad, India - Mihir Goswami; Geeta Kedia (Medsci Publications, 2010)
Background: In cites of India, at least one fifth people live in slums and most of the health problems as well as environmental issues are generated from these slums only. Objectives: To study the socio-demographic and environmental profiles as well as magnitude of morbidity among urban slum dwellers. Materials and Methods: The cross sectional study had been carried out between January 2000 and December 2000 on non-randomly selected 1,389 slum dwellers of Ahmedabad. Information was obtained by interviewing the head and/or other family members. General physical examinations and history of illness present in previous two weeks were recorded. Results:  There were no sanitary latrines and drainage facilities at studied slum. There were 987 females per thousand males and 903 females per thousand males in under five year age group. The literacy rate was 16.8 % and 5.6% among males and females respectively. Among five years above age males, 27%, 9.7% and 7.4% had a habit of smoking, tobacco chewing and alcohol intake respectively. Among five years above age females 4.36 %, 10.9% and 0.84 % had a habit of smoking, tobacco chewing and alcohol intake respectively. Out of 233 eligible couples, 11.16% and 24.46% were adopted spacing and permanent methods for contraception respectively.  28 % males and 33.7% females were either suffering from or have a history of one or more illness within previous two weeks. The morbidity rate for both sexes was 30.88%. Anemia was found in 19% of females of age group of 15-44 years. Respiratory tract infections and diarrhoea were present in7.4% and 3.7% of studied population respectively. The incidence rates for respiratory tract infections and diarrhoea were found higher among 0-4 year age group children (15% and 10.6% respectively). Conclusions: Slum clinic or mobile clinic van should be arranged for treatment of common morbidities and health promotional activities.